The Practice of Qurban: Integrating Economic, Social, and Environmental Dimensions - Basyir, Damanhuri (El-Sunan: Journal of Hadith and Religious Studies, 2024)
Qurban worship is one of the essential rituals in Islam, encompassing not only a spiritual dimension but also significant economic, social, and environmental impacts. Observed annually during Eid al-Adha, the practice of Qurban reflects the obedience of Muslims to Allah SWT's command and serves as a tangible manifestation of sacrifice and social care. This study aims to analyze the concept of Qurban from a broader perspective by integrating economic, social, and environmental dimensions. The article examines how Qurban functions not only as a ritual act of worship but also as a mechanism for fostering social welfare and economic equity through the distribution of meat to underprivileged communities. Additionally, the environmentally friendly management of Qurban animals is highlighted as a crucial factor in promoting environmental sustainability. The research method utilized in this study is library research, involving a review of academic literature and relevant documents, as well as an analysis of Qurban practices in diverse regions. The findings reveal that Qurban has the potential to reduce economic disparities, strengthen social solidarity, and enhance community awareness regarding environmental conservation. The integration of Qurban with these three dimensions can deliver broader benefits to society, ensuring that the values inherent in Qurban extend beyond spirituality to positively impact social, economic, and environmental well-being.